"حاضنات الأعمال الجامعية ودورها في مرافقة وتحسين أداء المؤسسات الناشئة " - عبد العزيز العايب; سفيان جوان; سفيان رحال (جامعة الوادي university of eloued, 2024)
"تهدف هذه الدراسة معرفة الدور الذي تلعبه حاضنة الأعمال الجامعية بالوادي في مرافقة وتحسن أداء المؤسسة الناشئة HB Tronics بالوادي ومن أجل الوصول إلى هذا الهدف تم اعتماد المنهج الوصفي من خلال جمع البيانات وتحليلها الخاصة بكل من حاضنات الأعمال الجامعية والمؤسسة الناشئة بالوادي. وخلصت هذه الدراسة إلى عدة نتائج من بينها: أن حاضنة الأعمال بالوادي تسعى لدعم وتطوير المشاريع المبتكرة من طرف الطلبة والمتكونين في مجالات متعددة، ودمجهم في الميادين . كما أن حاضنة الأعمال بالوادي رافقة المؤسسة محل الدراسة في جميع المراحل منذ أن كانت كفكرة إلى غاية خروجها كمؤسسة ناشئة، وبداية عملها في السوق. " "This study aims to learn about the role played by the University Business Incubator in the valley in accompanying and improving the performance of the emerging institution HB Tronics in the valley. In order to achieve this goal, the prescriptive curriculum was adopted through the collection and analysis of data for both university business incubators and the emerging institution in the valley. The study found several findings, including: The Valley Business Incubator seeks to support and develop innovative projects by students and constituents in various fields and integrate them into the fields. The Wadi Business Incubator is accompanied by the institution, which has been under consideration at all stages from the time it was conceived until its exit as an emerging institution, and its start in the market "
Keywords: حاضنات الأعمال الجامعية /المؤسسة الناشئة/ HB Tronics الملخص باللغة الأجنبية : University business incubators/startup/HB Tronics